(untitled) (Research, Society and Development, 2022)
Precision Farming systems adopt various high-tech equipment in hardware, software and communication to collect data from different sources in order to measure and evaluate all aspects of agricultural production. This management strategy allows the rationalization in the use of agricultural resources, increasing production efficiency while reducing the negative impacts of the activity in the field. This study aimed to monitor the technologies associated with Precision Farming, from the analysis of information from patent documents, in order to investigate the status and trends, as well as to identify the main providers and their collaboration networks. Research questions were formulated to guide the study, and this study is both quantitative and descriptive, and qualitative and exploratory in nature. The study also provides a methodological flow supported by free software tools for data collection, processing and visualization. Among the main results, the following stand out: 312 patent families filed by 303 applicants and 968 inventors were identified; 86% of the patent publications occurred in the last decade with an increasing trend; technologies were filed in 23 countries, with China and the United States standing out; about 86% of the holders and inventors own only one patent; planting, data processing and soil property analysis are the most developed technological sectors; highly cited patents; main inventors participate in a more cooperative way than the holders, being bridges between different groups of inventors.